A Highly Efficient Synthesis of Polyubiquitin Chains. Issue 7 (14th May 2018) - Qu, Qian; Pan, Man; Gao, Shuai; Zheng, Qing‐Yun; Yu, Yuan‐Yuan; Su, Jia‐Can; Li, Xiang; Hu, Hong‐Gang
Abstract: A robust, microwave‐assisted, highly efficient, solid‐phase peptide synthesis method for preparing isopeptide‐linked 62‐mer and 76‐mer isoubiquitins and polyubiquitin is developed. The strategy avoids the use of costly resins and pseudoprolines, and the isopeptide‐linked building blocks can be assembled with high initial purity within 1 day. All seven diubiquitins are successfully synthesized on a multi‐milligram scale; a four‐segment, three‐ligation method is used to obtain a K33‐/K11‐linked mixed triubiquitin in excellent yield. Circular dichroism and crystallographic analyses are used to verify the structures of the well‐folded, synthetic polyubiquitin chains. The facile synthetic strategy is expected to be generally applicable for the rapid synthesis of isopeptide‐linked isoUbs and to pave the way for the study of longer polyubiquitin chains. Abstract : A robust and highly efficient, high‐efficiency solid phase peptide synthesis–based strategy for the synthesis of isopeptide‐linked 62‐mer and 76‐mer isoubiquitins, various diubiquitins, and K33‐/K11 mixed triubiquitin is developed. The facile synthetic strategy is expected to be generally applicable for the rapid synthesis of isopeptide‐linked isoubiquitins and to pave the way for the study of longer polyubiquitin chains.